Nanodot Gradients: Large Dynamic Range Digital Nanodot Gradients of Biomolecules Made by Low‐Cost Nanocontact Printing for Cell Haptotaxis (Small 19/2013). Issue 19 (4th October 2013) - Ricoult, Sébastien G.; Pla‐Roca, Mateu; Safavieh, Roozbeh; Lopez‐Ayon, G. Monserratt; Grütter, Peter; Kennedy, Timothy E.; Juncker, David
<x xml:space="preserve">Abstract</x> D. Juncker and co‐workers report on page 3308 a rapid and low‐cost lift‐off nanocontact printing process to pattern proteins onto surfaces with 100‐nm resolution, and using a novel algorithm, create digital nanodot gradients (DNGs) with an unprecedented dynamic range of 3.2 orders of magnitude. Cell adhesion and directed migration on DNGs are observed, indicating that they may be used for quantitative cell biological studies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>